Nutritional outcomes with radiotherapy for head and neck cancer: A before and after comparison of 'best practice guidelines' implementation - Jeffery, E.; Young, P.; Sherriff, Jill (HEC Press, 2018)
© 2018, HEC Press. Background and Objectives: Malnutrition is prevalent amongst people with head and neck cancer treated with radiotherapy and can result in reduced tolerance to treatment and increased hospital admissions. Current bestpractice guidelines recommend weekly dietetic review during radiotherapy and fortnightly review for six weeks following radiotherapy to minimize weight loss. The primary aim of this study was to compare percent weight loss during radiotherapy before and after the implementation of weekly dietetic review. In the post-guideline implementation group we aimed to investigate factors associated with greater weight loss and describe weight changes 4-8 weeks post radiotherapy. Methods and Study Design: Adults with head and neck cancer who received dietetic input and curative intent radiotherapy were included. Data were collected via retrospective chart audit of records from the Nutrition and Dietetics department. Results: The analysis involved 142 people, 66% (n=94) of whom received dietetic input in the post-guideline implementation period. Mean weight loss was not different between the pre- and post-guideline implementation groups (-5.9±6.34% vs -6.6±5.29%; p=0.477). In the post-guideline implementation group, advanced tumor stage and concurrent chemoradiation were associated with greater percent weight loss (p=0.006 and p < 0.001, respectively). Mean weight loss increased by 1.9±4.96%, 4-8 weeks after radiotherapy (p=0.004). Conclusions: Percent weight loss during radiotherapy was not reduced following the implementation of weekly dietetic review. In the 4-8 weeks following radiotherapy, weight loss increased significantly over that between baseline and end of radiotherapy. Future research should explore and address the reasons why critical weight loss occurs despite improved access to dietetic care.